The Significance of Sukuk in Facilitating Small and Medium Enterprises (SMEs) - LONE, AIJAZ BASHIR; ABBAS, MUHAMMAD HASSAN (International Journal of Islamic Economics and Governance, 2022)
Small and medium-sized enterprises (SMEs) play a crucial role in fostering economic growth and generating job opportunities. However, these enterprises face many obstacles when seeking external funding. This paper aims to analyze the current developments in the funding alternatives accessible to small enterprises. In the process of assessing the barriers to obtaining foreign loans, we also analyze the function of Sukuk, which has seen a notable increase in importance within the Islamic financial system. Sukuk refers to a kind of debt instrument that does not include the accrual of interest, in contrast to traditional bonds. The Sukuk market exhibits distinctive characteristics, including securitization and real return on assets, which distinguish it from other financial markets. Nevertheless, small and medium-sized enterprises (SMEs) have challenges in accessing affordable financing options from the market. The objective of this study is to provide insight into the obstacles encountered by small and medium-sized enterprises in their pursuit of financial resources. Additionally, there are potential strategies to alleviate the aforementioned issues. This report also assesses the novel finance methods that leverage state-of-the-art technical advancements. This paper elucidates the economic ramifications of the sukuk market and its integration into the blockchain network.